A formação continuada e a percepção dos professores que realizaram o curso melhor gestão, melhor ensino – formação de professores de ciências - Lourenço, Sidney Cabral (2016)
This present study investigates the teachers participating in the process of implementation of teachers training policies and curricular policies of the SEE-SP, taken here as those who are in the process end – want to receive the training, want to act as implementing agents to exercise teaching in the classroom. The goal pursued was to map and interpret the perceptions, impressions and elaborations of teacher on the continuous training policies of the SEE-SP, on the State curriculum, on aspects of professional practice and on the participation in the Enhance Management and Education (MGME) as teacher students. The research focuses on a public school located in the city of São Paulo, having as subject two Science teachers who attend the MGME course in 2013 It uses the qualitative methodology and the instruments of collection of data are semi-structured interviews, questionnaire with open questions and a analysis of official documents governing the Program. The research is based on the following authors: Bioto-Cavalcanti, Carvalho, Day, Gatti, Hargraves, Imbernón, Moreira, Nóvoa, Lahire. The collected datas allowed a reflection on the continued training and the implementation of Official Curriculum of the São Paulo State. At the same time, it presents a documental overview of course 1 Enhance Management and Education (MGME) – Training of Trainers and of course 2 Enhance Management and Education (MGME) – Training of Science Teachers, emphasizing the course 2. Finally, parts of the interviews, highlighting the perceptions of the course and the execution in the classroom.